Pelatihan Literasi Numerasi Santri Melalui Kegiatan Himatika Mengajar - Muhammad Najib Mubarrok; Ahmad Anis Abdullah; Robiatul Adawiya; Dyahsih Alin Sholihah; Rino Richardo; Abdus Sholihin (BADAN PENERBIT STIEPARI PRESS, 2023)
Indonesia is a nation that prepares its human resources to face the times. Many preparatory efforts have been made, one of which is the numeracy literacy movement since 2016. As a form of support for the numeracy literacy movement, this community service aims to improve the numeracy literacy skills of students through Himatika Mengajar activities. The participants are MA As Salafiyah Mlangi students who are also santris from several Islamic boarding schools in the Mlangi area, Sleman. The method used in this service is the habituation of numeracy literacy-based questions. The result of this service is that santris become familiar with numeracy literacy-based problems and provide insight for santris to apply numeracy literacy skills in everyday life.